2020
DOI: 10.3389/fmicb.2020.537813
|View full text |Cite
|
Sign up to set email alerts
|

Local Conditions Influence the Prokaryotic Communities Associated With the Mesophotic Black Coral Antipathella subpinnata

Abstract: Black corals are important habitat-forming species in the mesophotic and deep-sea zones of the world’s oceans because of their arborescent colony structure and tendency to form animal forests. Although we have started unraveling the ecology of mesophotic black corals, the importance of the associated microbes to their health has remained unexplored. Here, we provide in-depth assessments of black coral-microbe symbioses by investigating the spatial and temporal stability of these associations, and make comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 134 publications
(180 reference statements)
2
25
0
Order By: Relevance
“…These recycling organisms are unlikely to be Symbiodiniaceae as our fragments seemed to be azooxanthellate (based on histological and metabarcoding analyses, data not shown). Several studies revealed the high diversity (Liu et al, 2018;Santiago-Vázquez et al, 2007) and plasticity (van de Water et al, 2020) in microbial communities associated with antipatharian corals, which role in nitrogen cycling within the holobiont has been demonstrated previously in scleractinians (Middelburg et al, 2016;Szmant et al, 1990;see Rädecker et al, 2015 for review). Here, microbial diversity was not investigated genetically, but histological analyses revealed the presence of cell-associated microbial aggregates (CAMAs) in the ectoderm of the tentacles (Figure 6b).…”
Section: Effects Of Temperature On Coral Metabolismmentioning
confidence: 56%
See 2 more Smart Citations
“…These recycling organisms are unlikely to be Symbiodiniaceae as our fragments seemed to be azooxanthellate (based on histological and metabarcoding analyses, data not shown). Several studies revealed the high diversity (Liu et al, 2018;Santiago-Vázquez et al, 2007) and plasticity (van de Water et al, 2020) in microbial communities associated with antipatharian corals, which role in nitrogen cycling within the holobiont has been demonstrated previously in scleractinians (Middelburg et al, 2016;Szmant et al, 1990;see Rädecker et al, 2015 for review). Here, microbial diversity was not investigated genetically, but histological analyses revealed the presence of cell-associated microbial aggregates (CAMAs) in the ectoderm of the tentacles (Figure 6b).…”
Section: Effects Of Temperature On Coral Metabolismmentioning
confidence: 56%
“…The skeleton of antipatharians is made of chitin and proteins (Goldberg, 1978;Goldberg, 1994;Juárez-de la Rosa et al, 2012;Kim et al, 1992) and is sought to be used for medical, religious or decorative purposes, or sold as precious corals in the jewellery trade in several regions across the globe (Bruckner et al, 2008;Bruckner, 2016;Grigg, 2001;Tsounis et al, 2010;Todinanahary et al, 2016). Diverse microbial communities were described within and around antipatharian tissues (Dannenberg et al, 2015;Liu et al, 2018;Penn et al, 2006;Santiago-Vázquez et al, 2007;van de Water et al, 2020;Zhang et al, 2012). They are known to play significant roles in antipatharian health, and may be a key player for acclimatization and/or adaptation to future environmental changes (Bosch & McFall-Ngai, 2011;McFall-Ngai et al, 2013;van de Water et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies feature 16S rRNA gene amplicon sequencing to describe the microbiome of corals. Large datasets, such as obtained for the Earth Microbiome Project, maximize the comparability among studies (Thompson et al, 2017), but the employed primers are prone to misamplification in corals and provide limited coverage of some taxonomic groups (Bayer et al, 2013;Robbins et al, 2019;van de Water et al, 2020). Such methodological constraints may resolve in the near future with the availability of direct full-length sequencing of 16S rRNA genes (Carradec et al, 2020).…”
Section: The Prokaryotic Communitymentioning
confidence: 99%
“…The different entities of fishing disturbance could also be linked to different coral morphologies. In fact, the morphological characteristics (arborescent and erect structures) and the grade of flexibility of black corals may increase their resistance to mechanical friction, showing different mechanical responses to their entanglement [24,43,65].…”
Section: Anthropogenic Factors Affecting Black Coralsmentioning
confidence: 99%